DIVERSITAS SPESIES BURUNG DALAM PENENTUAN KUALITAS RUANG TERBUKA HIJAU DI UNIVERSITAS LAMPUNG - Badia Roy Ricardo Nababan; Sugeng P. Harianto; Agus Setiawan (Lambung Mangkurat University-Indonesia, 2021)
University of Lampung (Unila) is one of the Green Open Space (GOS) in Bandar Lampung City which has vegetation. Vegetation in green open space has a role as a wildlife habitat for example birds. Various bird species can be indicators of the quality of open green space at the University of Lampung. This research was conducted to determine the diversity of bird species and as an indicator in determining the index of green space quality at the Unila Campus. Research is conducted from November 2016 to March 2017 and December 2018. The study was conducted at the Unila Campus which is divided into eight blocks. An inventory of the diversity of bird species carried out with concentrated observations in eight blocks. The value of diversity of bird species uses an analysis of shannon-wienner heterogeneity index value and the quality of green open space through the calculation of green space quality index values. Based on the results of the study there were 20 species of birds on the Unila campus. The diversity index of bird species is classified as moderate (H '= 2.74). The GOS quality index at the Unila Campus is 59.2 with the intermediate category.